China's path of human rights development - Liu, Huawen (Springer, 2022)
This book focuses on China's evolution in the field of human rights protection, highlighting its achievements in various systems of human rights protection, as well as its role in international human rights governance and the healthy development of human rights. From the perspective of China's human rights protection, starting with various types of citizens, e.g. women, children and the disabled, the book analyzes and discusses the changes and major events in the country's human rights development path one by one, while also explaining the Chinese stance on human rights development. China is becoming more active in the international human rights cooperation field, playing its unique and constructive role and serving as the participant, builder and contributor of the international human rights governance
Translated from the Chinese
Keywords: Menschenrecht; China; Human rights / China; International law and human rights